An Analysis of the English Speaking Anxiety at the Eleventh-Grade Students of SMK Muhammadiyah 1 Palu - Suratul Marsela; Andi Naniwarsih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
An Analysis of the English-Speaking Anxiety of the Eleventh-Grade Students of SMK Muhammadiyah 1 Palu. This research aims to discover the factors that cause the eleventh-grade students of SMK Muhammadiyah 1 Palu to feel anxious about speaking English. This research employs a descriptive-qualitative design. In collecting data, the researchers used interviews and questionnaires. The data analysis is data reduction, data display, and data verification. From the data analysis, the research found the factors that cause students to feel anxious when speaking English: fear of being laughed at by others, mispronunciation, lack of vocabulary, fear of making mistakes, fear of speaking in public, lack of self-confidence, and low language skills.